2018
DOI: 10.1097/brs.0000000000002671
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Rod Lengthening, Thoracic, and Spino-Pelvic Measurements on Biplanar Stereoradiography in Patients Treated With Magnetically Controlled Growing Rods

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…34 A validated predictive model of correction rate using supine flexibility has also been established for thoracic curves. 13,35 Our findings on the predictive ability of flexibility and correction rate largely coincide with the literature. [11][12][13] We have shown that high correction rate and flexibility are significantly predictive of brace success after adjusting for commonly assessed radiological predictors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…34 A validated predictive model of correction rate using supine flexibility has also been established for thoracic curves. 13,35 Our findings on the predictive ability of flexibility and correction rate largely coincide with the literature. [11][12][13] We have shown that high correction rate and flexibility are significantly predictive of brace success after adjusting for commonly assessed radiological predictors.…”
Section: Discussionsupporting
confidence: 87%
“… 34 A validated predictive model of correction rate using supine flexibility has also been established for thoracic curves. 13 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, the prevalence of PJK is high with up to 30% in some reports but not all require reoperation (approximately 15%). 28,[41][42][43][44] In general, the proximal levels of T1 or T2 should be avoided if possible as more cranial levels may be needed in the final fusion surgery to address the PJK. Conversion to rib anchors may help prevent these complications and has been well-established in TGR surgery.…”
Section: Anchorsmentioning
confidence: 99%